Einfluss sozialer Präferenzen auf die Steuerung dezentraler Einheiten - Kai Sandner (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2006)
– Economic theory typically assumes that people are only interested in their own material wealth. Experimentalists have recently discovered that this assumption is not true under all circumstances. Especially in regular face to face interactions, not only the personal well-being but also the well-being of other people is important for individual decisions. These findings are particularly important for the design of incentive systems to control the behaviour of managers of decentralized organizational units since managers and entities repeatedly interact in order to achieve the superordinate enterprise goals. In this context social preferences such as jealousy, spitefulness and reciprocity can influence managerial behaviour on the vertical as well as the horizontal organizational layer. The appropriate design of incentive compatible wage compensation systems has to take into account that people are behaviourally different and consequently respond differently to incentives. The main goal of the paper is to analyze how the principal should react to the different behavioural traits of his agents in order to guarantee the achievement of the superordinate enterprise goals. Of particular interest is the impact of jealousy and spitefulness between horizontally aligned agents on the weighting and combination of performance measures. The cases stochastical independence/dependence as well as technological independence/dependence are differentiated throughout the analysis.
urn:nbn:de:bvb:19-epub-1230-4
Keywords: M41; M52; 650; social preferences; jealousy; spitefulness; performance measurement; multi-agent; technological dependencies; stochastical dependencies